Transcriptomic and functional profiling of Acinetobacter baumannii reveals adaptation to burn patient blood and time-dependent responses to human serum - Ghavanloughajar, Hannaneh; Brown, Amanda M. V.; Deonarine, Amrika; Wang, Yongli; Hamood, Abdul N. (Frontiers in Microbiology, 2025)
Acinetobacter baumannii is a critical threat to immunocompromised patients, particularly those with burn injuries. Despite its clinical significance, little is known about how this bacterium adapts to the complex environment of burn patient blood, which differs significantly from that of healthy individuals. To address this, our methods included analyses of a blood-isolated strain of A. baumannii A118 grown ex vivo in whole blood from healthy volunteers (WBHV) and burn patients (WBBP). Transcriptomic analysis revealed host-specific expression patterns, including the downregulation of acinetobactin siderophore genes in WBBP—suggesting increased free iron levels—and the strong upregulation of nitrate/nitrite metabolism genes, indicating altered nitrogen availability in burn patients’ blood. Since serum makes up the majority of blood volume and contains key factors influencing bacterial physiology, we examined the transcriptomic response of A. baumannii to pooled human serum in an LB + 10% serum model at two different time points of growth, isolating the impact of soluble components free from immune cells and building on patterns seen in whole blood. Consistent with our ex vivo findings, we again observed dynamic regulation of the acinetobactin operon—this time in response to serum exposure: an initial upregulation of key iron uptake genes at early time points was followed by strong downregulation later, suggesting a transient iron starvation response that is modulated as intracellular iron accumulates, which can be supported by our ICP-MS results, revealing increased intracellular iron and other metal ions in serum-treated bacteria over time. To support additional serum-induced transcriptomic findings beyond acinetobactin, we used multiple experimental approaches: LC–MS/MS of outer membrane protein (OMP) extracts identified a serum-upregulated acinetobactin transporter; and phenotypic assays revealed that serum enhanced biofilm formation, increased twitching motility, elevated mortality in the Galleria mellonella infection model, and raised minimum inhibitory concentration (MIC) for multiple antibiotics. In conclusion, these findings expand our understanding of pathogen behavior in clinically relevant conditions and suggest that host-specific blood physiology—especially in burn patients—can shape the course of infection.